Systematic review of the effect of Phyllanthus emblica in glycaemic control - Upeksha Gayani Karawita; Sarasi Withana; Shanaz Thasleem; Jinadari Amarasena; Buddhika Mahesh; Mahendra Arnold; Ruwan Ferdinando; Wasantha Gunathunga (College of Community Physicians of Sri Lanka, 2023)
Introduction: Diabetes mellitus which is characterized by chronic hyperglycaemia accounts for 1.6 million deaths per year globally. In Sri Lanka, 7.4% of adults are with raised fasting blood glucose. Phyllanthus emblica, some fruit, which is also called by Nelli, Amla or Indian Gooseberry, is traditionally believed to facilitate control of hyperglycaemia. Objectives: To systematically review the glycaemic control effect of Phyllanthus emblica. Methods: PubMed, EMBASE, Cochrane Library, CINAHL and AGRICOLA databases were searched to select relevant studies. Studies were selected in two rounds. Three screening questions consisted of; whether study was a human study with Phyllanthus emblica included as a fruit or an ingredient, outcomes were related to glycaemic control and outcomes being reported quantitatively. Following the review of titles and abstracts, full articles were reviewed with screening questions such as, study design, participants, intervention, and findings of outcome. Two reviewers independently screened articles with the third intervening in resolving the conflicts. Meta-analysis was not performed following the heterogeneity assessments and narrative review of the findings was done. Results: Eighteen studies were selected, having respectively excluding 81, 106 and 22 studies with reference to three screening questions. Six studies were done among healthy individuals and 12 were done among patients with diabetes. The studies were conducted among the age group of 18-75 years. Sample sizes of studies ranged from 10 to 150 participants, with 951 participants in total. In three studies, Phyllanthus emblica was used as a single entity and in 15, it was one component of a combined product. Fifteen selected studies described the mean fasting blood sugar (FBS) levels and 13 of them showed statistically what Phyllanthus emblica or products containing it had on glycaemic control, compared to control group (p<0.001). Out of those 13 studies with significant findings on glycaemic control, 10 studies were done among hyperglycaemic patients. In eight studies, a significant reduction in HbA1c results (p <0.05) was observed and nine studies showed a significant reduction in post prandial blood sugar (PPBS) levels (p<0.05). None of the selected studies showed any negative impact of Phyllanthus emblica on blood glucose levels among either healthy or diabetics individuals. Conclusions & Recommendations: Phyllanthus emblica is found to be with favourable effects in facilitating blood sugar control. Further research on the potential application of it as a glycaemic controller, must be encouraged.